RESEARCH INTO FLOWS IN TURBINE BLADE SEALS PART II: NUMERICAL ANALYSIS - ROBERT STĘPIEŃ; KRZYSZTOF KOSOWSKI; JANUSZ BADUR (TASK Quarterly, 2003)
3D calculations of an axial model turbine of the impulse type were performed using the FLUENT CFD code. The calculations were carried out for variants which had been measured experimentally. Special attention was paid to the pressure field in the rotor blade shroud clearance. The Multiple Reference Frame method, the Mixing Plane method and the Sliding Mesh method were applied, and meshes of different types and configurations were used for calculations. Only the Sliding Mesh technique appeared to describe non stationary effects and pressure pulsations in the turbine flow channels and clearances. In this part of the paper, numerical analysis is described, while the comparison between the experimental and the calculated results is presented in part III.